(3QSGdI aj GdEQKs - (3eLghds ((3cQje Hf Ydjs)
(3ChdgG (B:s
(3HSe Gddg (B... (3eSCdI dh eGJ TNU hNda CMO GdCHhjf hHfJG fUjH CMO GdCHhjf GdSOS hfUjH GdHfJ GdfUa hCbd aQjVI jLJeY ajgG GdfUa ef SfI aGUd GdaQjVI SfI aGUd GdaQjVI SfI hGMO efgG (B...s
(3BNQgG (B:s
... (3hEPG aQV GdNfKi CfKi cGf fUjHg ef CQHYjf YTQ hIecPdc GdCfKi hddPcQ YTQhf ajCNP gDdGA GdePchQhf fUa GdeLehY ajMUd GdNfKi KeGfjI YTQ Jes
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis